THE COMPARISON OF FAULT DETECTION RESULTS ON ROTATING MACHINERY USING VIBRATION AND SHOCK PULSE METHODS - Keith Anggarawan, Hansel
Condition monitoring of rotating machinery is often conducted in industries to detect and prevent component failures. There are several methods commonly used to monitor the condition of rotating machinery components. Among these methods are vibration and shock pulse method. Both methods have their unique advantages. However, only a few studies have compared the damage detection results using these two methods. Additionaly, these studies have relied solely on experimental data from laboratories, not on data measured in industries. Therefore, this research aims to compare the damage detection results of rotating machinery using vibration and shock pulse methods, both on data measured in the laboratory and in the industry. This research began by conducting measurement using the two aforementioned methods on a testing equipment available in the Dynamics Laboratory. The testing equipment was a rolling element bearing damage test apparatus. The condition of the bearing was varied to make the comparison of detection results more comprehensive. The measurement results from both methods were then analyzed and compared. The next step of this research was to analyze the measurement results from both methods on a wire-drive gearbox in a paper industry. The gearbox consists of two pairs of gears and has a rotational speed input that can be varied. Subsequently, some of the available vibration and shock pulse data were analyzed and compared. The comparison of damage detection results using the two aforementioned methods for the rolling bearing damage case indicates that the shock pulse method is able to detect damage on the bearing more clearly than the vibration method. Meanwhile, the comparison of damage detection results for the wire-drive gearbox indicates that the vibration method is better at monitoring the condition of the gears compared to the shock pulse method.